Antibacterial Effect of Longan Extract and Diode Laser Combination on Peptostreptococcus Species in Type 2 Diabetic Patients with Apical Periodontitis - A Pilot Study: Life Sciences-Periodontitis for Dental health - Dr. Moksha Nayak; Dr. Angeline Jose; Dr. Vidhya Shenoy (International Journal of Life Science and Pharma Research, 2022)
Diabetes mellitus is a risk factor for developing periapical infections and increases resistance against pharmacotherapy. Microorganisms are the major cause for periradicular diseases. Peptostreptococcus spp. is the most common bacterial isolate from root canals of primary endodontic infections in diabetic patients. Herbal irrigants are being researched for its efficacy against root canal microorganisms owing to their resistance against commonly used irrigants and medicaments. Longan extract is known for its antimicrobial and antiglycemic action. Diode laser is a newer modality in the disinfection of root canal system. The aim of this study was to assess the antibacterial effect of longan extract (longan fruit extract) and diode laser on Peptostreptococcus species in type 2 diabetic patients with primary endodontic infections using PCR technique. Eleven subjects with type 2 diabetes requiring endodontic treatment were selected for the study based on convenience sampling for a period of 3 months. The preoperative root canal samples were collected after gaining access to the root canal system and initial instrumentation of root canals. Postoperative sample were obtained following a disinfection protocol using 3% NaOCl, 17% EDTA, longan extract as the final irrigant, followed by diode laser irradiation. Both the preoperative and postoperative samples were collected as per Moller’s criteria using sterile paper points. The mean percentage reduction following irrigation of the root canal with longan extract was 71.18% whereas diode laser showed 100% disinfection. In conclusion, the combination of longan extract and diode laser provides an effective mode of root canal disinfection in type 2 diabetic patients with apical periodontitis.